THE HUMAN PROBLEM IN EASTERN AND WESTERN PHILOSOPHY - Rasulov Ortiq (Journal Park Publishing, 2023)
The article analyzes the initial foundations of philosophical reflection of the image of a person and his inner world, which received its historical and philosophical expression in the modes of world cultures of Europe and the West. Based on comparative analysis, reconstruction of three philosophical approaches – hermeneutic, philosophical historicism and metaphysical in modern orientalism. Methodology Philosophical comparative studies is intended to substantiate the diversity of world philosophy and to supplement existing ideas with dialogue. It is noted that an existentialist version of reading philosophical thought is being formed in the East. If the European West symbolizes will, activity and rational achievement of goals, then the East symbolizes inaction, humility and detachment.
Keywords: human, East and West, philosophy, philosophical comparative studies, philosophy of the European West and East, Buddhist philosophy of non-existence.